2020
DOI: 10.1038/s41385-019-0248-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing analysis reveals alginate oligosaccharides preventing chemotherapy-induced mucositis

Abstract: Worldwide the incidence of cancer has been continuing increasing. Mucositis of the gastrointestinal tract is a common side effect in patients under chemotherapy. Anticancer drug busulfan, used for treating chronic myeloid leukemia especially in pediatric patients, causes mucositis of the gastrointestinal tract. Alginate oligosaccharides (AOS) are natural products with attractive pharmaceutical potentials. We aimed to investigate, at the single-cell level, AOS preventing small intestine mucositis induced by bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 44 publications
5
58
0
Order By: Relevance
“…Regular FMT involves the transplantation of fecal material from a healthy donor into a diseased recipient [8]. However, we found that AOS also rescues busulfan-impaired gut microbiota in the small intestine [23]. We hypothesize that FMT from AOS-dosed mice might alleviate small intestine disruption following recipient chemotherapy to a greater extent than FMT from control animals.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Regular FMT involves the transplantation of fecal material from a healthy donor into a diseased recipient [8]. However, we found that AOS also rescues busulfan-impaired gut microbiota in the small intestine [23]. We hypothesize that FMT from AOS-dosed mice might alleviate small intestine disruption following recipient chemotherapy to a greater extent than FMT from control animals.…”
Section: Introductionmentioning
confidence: 81%
“…In a recent report, we revealed that AOS mitigated small intestine cell membranes damage especially cell junctions and microvilli by the anticancer drug busulfan; simultaneously, AOS supported the blood metabolome to assist small intestinal recovery [23]. This is because gut microbiota can metabolize nutrients and also regulate intestinal metabolites to affect the blood metabolome [35,36].…”
Section: Aos Benefited Gut Microbiotamentioning
confidence: 92%
See 3 more Smart Citations